ANALISIS TINGKAT BAGI HASIL, INDEKS SAHAM JII DAN PERTUMBUHAN EKONOMI TERHADAP DEPOSITO MUDHARABAH PADA PT BANK SYARIAH MANDIRI DI INDONESIA - Hamdani Hamdani; Mizan Mizan; Nusyidah Nursyidah; Rahmi Raihan; Aura Humayrah (Politeknik Negeri Lhokseumawe, 2020)
he development of Mudharabah Deposits in conventional and sharia banking is increasingly becoming a choice and getting a positive response from consumers. Mudharabah time deposits are an important component for Islamic banks in collecting funds from the public as an investment. This study aims to conduct an analysis of the level of profit sharing and economic growth seen as an important factor in the development of mudharabah deposits. The data used in this study are secondary data, namely the data for the 2010-2019 quarter period contained on the official website of the Financial Services Authority (OJK), Yahoo Finance and the Central Statistics Agency. The object of research at PT Bank Syariah Mandiri in Indonesia. The analytical method used is multiple linear regression analysis. Based on the results of this study indicate that the level of profit sharing, JII stock index and economic growth simultaneously have a significant effect on mudharabah deposits. Partially the profit sharing rate and JII stock index have a positive and significant effect on mudharabah deposits. While economic growth partially has a significant negative effect on mudharabah deposits. This study is in line with previous studies and there are differences from previous studies. The results of this study can be used for subsequent studies that want to see the development of mudharabah deposits, especially in Aceh, which has implemented the conversion of conventional banks into Islamic banks. Keywords : Profit Sharing Rate, JII Stock Index, Economic Growth, Mudharabah Deposits